The role of ERP in business model innovation: Impetus or impediment - Francisco-Jose Molina-Castillo; Rocío Rodríguez; Carolina López-Nicolas; Harry Bouwman (Digital Business, 2022)
Purpose This research explores the moderating role of Enterprise Resource Planning (ERP) in (Business Model (BM) innovation by comparing two groups of Small and Medium-sized Enterprises (SMEs) that are still in the process of considering adoption of ERP or already have implemented ERP. In particular, the aim is to see whether ERP enables or hampers the relationship between BM experimentation, i.e. the process of BM innovation, and BM performance. An important mediator, with a focus on downstream value delivery and creation, is the novelty of the BM in question. Design/methodology/approach This research is based on a large quantitative study among Spanish firms that are engaged in BM innovation activities and in different phases of implementing ERP. A representative sample of 208 Spanish firms engaged in Business Model Innovation from different sectors was used to collect data, which was analysed using heterotrait-monotrait (HTMT) for scaling and Structural Equation Modelling (SEM) for model testing. Findings Quantitative findings show that there is a direct positive impact of BM experimentation on BM performance for firms that did not implement an ERP, while downstream novelty leads to improved value capture due to increased efficiency and the associated cost reduction. By contrast, firms with ERP show a better performance, depending on the degree of the downstream novelty of the BM. Originality/value There is no previous research exploring the moderating role of ERP in BM Innovation for SMEs. This is the first study to examine whether BM experimentation affects BM performance and value capturing, as mediated by BM novelty and moderated by implementation by ERP.
Keywords: 650; Enterprise resource planning; Business model innovation; Business model performance; Business model novelty; Business model value capture